KEBIJAKAN DAN INOVASI PENDIDIKAN ANAK USIA DINI (PAUD) DI ERA POST COVID-19 - Amanda Deswita Maharani; Nurhelina Risma Sari; Risma Rustianingrum; Rosa Octaviani; Esya Anesty Mashudi (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
The main purpose of analyzing policies and innovations in early childhood education in the post-Covid-19 era is to find out the trends or developments in policies and learning innovations in early childhood education during the post-Covid-19 era. The method used in writing this article is based on the Sysytematic Literature Review (SLR) method, the author analyzes several research journals systematically and thoroughly in obtaining theoretical references that can be a reference source. The results obtained from this research are knowing the impact of Covid-19 on early childhood education and care services, knowing how PAUD can recover from Covid-19, knowing the curriculum used during the Covid-19 pandemic and responding to challenges that arise in the education system after the Covid-19 pandemic to ensure that early childhood education can reach more children, especially those living in poor or rural areas.